The Social, Political, and Religious Values of Tolerance in School Textbooks of Kurdistan Region of Iraq: (History Textbooks as a Sample) - Beshkosh Jaafar Abdullah (International Journal on Humanities and Social Sciences, 2022)
This study aims to find out the political, social, and religious values of tolerance in school textbooks, specifically in history textbooks for the seventh, eighth, and ninth grades in Kurdistan Region. The research question is: what are the political, social and religious values of tolerance in the school textbooks for basic education? The methodology used to answer this question is, content analysis by taking paragraphs as well as direct and indirect concepts as units of analysis. The tool of the research is a list of values made by the researcher herself and by getting benefit from the literature review. The results showed that not all the values listed were present in the three textbooks and that these values were distributed randomly without considering their exigency.